2014
DOI: 10.5430/jct.v2n2p147
|View full text |Cite
|
Sign up to set email alerts
|

Using Teacher Questions to Enhance EFL Students’ Critical Thinking Ability

Abstract: In this era of information and economic globalization, developing critical thinking skills in college students has been set as a primary goal and learning outcome in higher education. Teaching critical thinking, however, is a great challenge to most EFL teachers. This article, therefore, attempts to examine the nature and teachability of critical thinking, analyze and discuss the functions and types of teacher questions as well as Bloom's Taxonomy of Questions. Its primary purpose is to help EFL classroom inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 23 publications
2
31
0
5
Order By: Relevance
“…More studies conducted in the field of reading, indicated that those instructional strategies which stimulate learners' higher levels of thinking like questioning strategies have been found to be successful in improving critical thinking skills. This is done through enhancing students' thought below the surface of things to push them to deal with more complex content (Marzuki, Alim, & Wekke, 2017;Samelian, 2017;Rashid & Qaisar, 2016;Lewis, 2015;Feng, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…More studies conducted in the field of reading, indicated that those instructional strategies which stimulate learners' higher levels of thinking like questioning strategies have been found to be successful in improving critical thinking skills. This is done through enhancing students' thought below the surface of things to push them to deal with more complex content (Marzuki, Alim, & Wekke, 2017;Samelian, 2017;Rashid & Qaisar, 2016;Lewis, 2015;Feng, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…These kinds of assessment will offer significant feedback for teachers as they support their students' development of HOTS. In addition, Feng (2013) states that EFL teachers should be experts at developing higher order questions to develop their students' critical thinking ability. He, further, says that the questions teachers ask decide the way in which their students' thinking goes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Wangru (2016, p. 144) states that teacher can use questioning to control the interactions that happen in the class since it can activate students' thought, expand students' recognition and maintain the students' to participate in the class. The role of teachers' questions in higher order, that is, questions that inscribe the top cognitive processes in Bloom's Taxonomy, i.e., analysis, synthesis and evaluation questions, in improving EFL students' critical thinking ability (Feng, 2013). As stated by Harmer (2000), it is a crucial part of the teacher to make the students speak using the language they are learning.…”
Section: Literature Reviewmentioning
confidence: 99%